Analisis Stakeholder dalam Pengendalian Kebakaran Hutan dan Lahan di Kabupaten Batang Hari Provinsi Jambi - Rinaldi Rinaldi; Asmadi Saad; Marwoto Marwoto (Universitas Batanghari Jambi, 2023)
Land and forest fire management including aspect; prevention, countermeasures, and handling post forest and land fire. All stakeholders have respective roles in each aspect and expected can contribute and collaborate so that efforts to control fire forests and land in the Batang Hari District can be done effectively and efficiently. There are 31 (thirty-one) stakeholders involved in the land and forest fire management in the Batang Hari District, such as the Technical Implementation Unit of the Ministry of Environment and Forestry, Government of Jambi Province, Government district of Batang Hari, Communities, Plantation and Forestry Entrepreneurs, Social Community Institutions, and Universities. Out of 31 (thirty-one) stakeholders, there are 14 (fourteen) stakeholders enter the category Keyplayer, there are 7 (seven) stakeholders have a role as Subject, 3 (three) stakeholders have a role as Context Setter, and 7 (seven) stakeholders play a role as Crowd.